Menumbuhkan Minat Baca dan Tulis Mahasiswa - Alwan Wibawanto (Pustakaloka, 2013)
Abstract: Today students had less motivation to study (reading/writing), whereas to be on the position had more expectation and more responsibility, and should give solution on problems of nations of worlds. Reading and writing are obligation, especially for students. Islam stated, that both of them are a heart of Islamic teachings, the first verse is Iqra’ (read), means to be muslims, someone must read. To develop this ability is studying to respect the image of book to be part of modern life, giving assignment like making short journal, paper, book critics, and other include on curriculum.